Alignment of qualitative and quantitative focus of attention assessment of stone delivery among high-level canadian curlers - Robak, N.; Zacharias, E.; Tailor, G.; Malone, Q.; Broeckelmann, E.; Mohammadalinezhad Kolahdouz, S.; Passmore, S. (International Journal of Sport and Exercise Psychology, 2025)
To understand the alignment of current focus strategies of high-level Canadian curlers and to investigate if the focus of attention theory differentially affects draw and takeout deliveries, a mixed-methods approach was used. Eleven high-level Canadian curlers (N = 11) delivered draws and takeouts of both handles (in-turn/out-turn) under control, internal focus, and external focus conditions. To prevent knowledge of performance and results, the curlers vision and hearing were occluded post-delivery. Pre-experiment questions pertained to the focus strategy. Post-experiment questions pertained to focus preference. Open-ended questions were analysed via thematic analysis. Draw radial error, absolute constant error, and variable error scores were analysed via separate repeated measures ANOVA with Tukey`s Honestly Significant Difference post-hoc test. Takeout end-point accuracy (hit/miss) were analysed by handle via a one-way Cochrane Q test with McNemars test as a post-hoc. Curler`s self-regulated focus strategy used a multifaceted focus approach with multiple internal and external foci. For draws, regardless of handle, an internal focus increased radial error compared to control. In contrast with actual performance, athletes favoured an internal focus due to the perceived importance placed on "touch". Conversely, athletes preferred an external focus for out-turn takeouts which increased hitting rate over an internal focus, and was favoured for the increased sensation of "line maintenance" which aligned with performance. Draw and takeout end-point accuracy were differentially affected by focus. A multifaceted attentional approach should be considered to align perception and performance.